Project Management for IT-Related Projects - Hughes, Bob.; Hughes, Bob.; Ireland, Roger; West, Brian; Smith, Norman; Shepherd, David I. (Swindon : BCS Learning & Development Limited, 2012)
Ideal for IT practitioners with project management responsibility, this book explains the principles of IT-related project management, covering key areas such as project planning, monitoring and control, change and risk management and communication between project stakeholders. It includes new material on risk assessment and agile approaches.
2.4 activity planning2.5 resource allocation; 2.6 using software tools for planning; sample questions; answers to sample questions; pointers for activities; 3 monitoring and control; learning outcomes; 3.1 introduction; 3.2 the project control life cycle; 3.3 monitoring progress; 3.4 applying control; 3.5 purpose and types of reporting meetings; 3.6 taking corrective action; 3.7 graphical representation of progress information; sample questions; answers to sample questions; 4 change control and management; learning outcomes; 4.1 introduction; 4.2 definition of change
Description based upon print version of record.
Keywords: Project management; Information technology -- Management; Electronic books